Drug-Herb Interaction between Metformin and Momordica charantia in Diabetic Mice - Asri Dwi Endah Dewi Pramesthi; Mirhansyah Ardana; Niken Indriyanti (Molecular and Cellular Biomedical Sciences, 2019)
Background: Bitter gourd has various metabolites, such as momordicosides, polypeptide-P, v-insulin, charantin, and vicine that have antidiabetic effect. It has synergistically effect while combined with oral diabetic drugs, such as metformin as glucose lowering agent. The aim of this study is to investigate the interaction of bitter gourd fruit juice and metformin as glucose lowering agent in mice.Materials and Methods: Alloxan-induced diabetic mice were treated with bitter gourd fruit juice, metformin, and the combination of those two for 21 days. Glucose level was checked on first and last day of treatment.Results: Furthermore, blood glucose levels measurement showed no significant difference between groups compared with negative control, which was p>0.05. The stomach of groups that treated with metformin and bitter gourd fruit juice histopathologically showed no significant differences.Conclusion: The use of bitter gourd once daily together with metformin is a better choice, while twice daily might induce hypoglycemia and mice death. There is no interaction between them on lowering blood glucose.Keywords: metformin, Momordica charantia, diabetes mellitus